How Does the Law Solve the Covid-19 Problem? - Hendro Cahyo Saputro (Universitas Negeri Semarang, 2020)
Covid-19 was first discovered in China precisely in Wuhan City, this virus first appeared in 2019 which then this virus spread throughout the world including Indonesia, which until now still struggling against the Covid-19 virus to date, the number continues to grow until many cause death, this has the effect of economic and other pressures and become a global problem. So the government must make new policies to overcome this problem. Activation of corporations both nationally and globally has received a very large impact as a result of the spread of the covid-19 virus, very rapid transmission rates, the risk of death for people who are weak immune to anti-virus that has not been found with certainty makes a number of countries and governments adopt policies that legally implicated because it is not only the main problem. Many problems arise such as the scarcity of APD and a lot of crime because it is related to an increasingly bad economy.